A comparative study of partogram in normal labour with and without a constant caring companion - Rajgire, Aditi; Borkar, Kiran; Rajgire, Aniket (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In today’s world with the concept of changing childbirth, where there is a ’women centered approach’, the idea of a constant caring companion has reemerged. In a busy labour ward patients may deliver safely but it may contribute to patient’s dissatisfaction, as they do not feel cared for. The constant caring companion would prove an important asset to the doctor and nurses involved in the management of the women in labour. Methods: Prospective study carried out in 120 patients meeting inclusion criteria. Results: Patients with constant caring companion had significant lower percentage (13.3%) of pain level as compared to those without companion. The mean satisfaction score of the patients with ccc was 90.66 whereas the score of the group without ccc was 30.33 which statistically highly significant. 42 of the patients with ccc and 39 patients without ccc opted for known female relative as constant caring companion. All woman in the study group and 97% in the control group would recommend a constant caring companion to the pregnant woman. Conclusions: Women with a constant caring companion have a more fulfilling and satisfactory experience of the labour process which cannot be said about the women without ccc. Since no negative impact was observed due to the presence of a constant caring companion, this practice may be recommended. The constant caring companion would prove an important asset to the doctor involved in the management of labouring women.